Irreversibility minimization of heat exchangers for transcritical CO2 systems - Sarkar J.; Bhattacharyya S.; Ram Gopal M. (My University, 2025)
Irreversibility analyses of both evaporator and gas cooler of a CO2 based transcritical heat pump for combined cooling and heating, employing water as the secondary fluid, have been reported. The analysis includes both operational and material associated irreversibilities. Optimization of heat exchanger tube diameter and length and effect of design parameters on overall system performance is also presented. Results clearly show that higher heat transfer coefficient can be achieved by reducing the diameter only to a limited extent due to rapid increase in pressure drop. The minimum possible diameter depends on mass flow rate (capacity) and division of flow path. The right combination of optimum diameter and length depends on the number of passes, capacity and operating parameters. It is noteworthy that due to higher pressure drop occurring in the evaporator compared to the gas cooler, zero temperature approach is attained before the optimum length is reached in case of the evaporator. Presented results are expected to help choose effective heat exchanger size in terms of diameter, length and number of passes. © 2008 Elsevier Masson SAS. All rights reserved.